2015
DOI: 10.2175/106143015x14212658613721
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Contaminant Loads from the Sacramento‐San Joaquin River Delta to San Francisco Bay

Abstract: Contaminant concentrations from the Sacramento-San Joaquin River watershed were determined in water samples mainly during flood flows in an ongoing effort to describe contaminant loads entering San Francisco Bay, CA, USA. Calculated PCB and total mercury loads during the 6-year observation period ranged between 3.9 and 19 kg/yr and 61 and 410 kg/yr, respectively. Long-term average PCB loads were estimated at 7.7 kg/yr and total mercury loads were estimated at 200 kg/yr. Also monitored were PAHs, PBDEs (two yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…This might be because the Houston watersheds have less urban development (14-89%), or because Suarez et al was unable to capture the peak discharge in all but two of 10 samples. In contrast, stormwater concentrations (average 0.022 ng/l) measured in the large and rural-dominated Sacramento River watershed at the head of San Francisco Bay (David et al, 2015) were similar to the low end of concentrations reported for the urban watersheds previously described.…”
Section: Dioxinssupporting
confidence: 82%
See 2 more Smart Citations
“…This might be because the Houston watersheds have less urban development (14-89%), or because Suarez et al was unable to capture the peak discharge in all but two of 10 samples. In contrast, stormwater concentrations (average 0.022 ng/l) measured in the large and rural-dominated Sacramento River watershed at the head of San Francisco Bay (David et al, 2015) were similar to the low end of concentrations reported for the urban watersheds previously described.…”
Section: Dioxinssupporting
confidence: 82%
“…Although highly urbanized, the Z4LA watershed contains no known PCB source areas; PCB transport in this watershed is likely more generally representative of older mixed urban and industrial land uses. In contrast, watersheds with known specific industrial sources appear to exhibit average concentrations in excess of about 100 ng/l (Hwang and Foster, 2008;Marsalek and Ng, 1989;McKee et al, 2012;Zgheib et al, 2011Zgheib et al, , 2012 and watersheds with little to no urbanization dominated by agriculture and open space exhibit average concentrations b5 ng/l (David et al, 2015;Foster et al, 2000a;Howell et al, 2011;McKee et al, 2012) (see Supplementary Information Figure S3). …”
Section: Pcbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, total PCBs in Houston, Texas, ranged from 0.00082 to 0.094 μg/L with a mean of 0.005 μg/L (Howell et al 2011 ). Concentrations of PCBs were particularly low (flow weighted average of 0.000340 μg/L) in the San Francisco Bay Delta, where the two major rivers feed the San Francisco Bay; the rivers drain mostly agricultural land and open space (David et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though humans require trace quantities of selenium for cellular functions, elemental selenium and selenite oxyanions are lethal in even small dosages (Fordyce, 2005). Due to the human activities, selenium contamination is considered to be the main environmental pollution found almost everywhere (soil, water) (David et al, 2015) Selenium has widespread uses in industrial and agricultural processes, which are responsible for its high toxic levels in the environment (Pierru et al, 2006). Microorganisms have been shown to play major role in the reduction of different Se oxyanions (Nancharaiah and Lens, 2015).…”
Section: Introductionmentioning
confidence: 99%